Pendampingan Penyusunan Dokumen Usulan Jabatan Fungsional Pertama Bagi Dosen Tetap Sekolah Tinggi Teknologi Bontang - Zaini Zaini; Hardianto; Lapu Tombil Layuk; Fiky Anggara; Ilham Maridi; Inas Umniyah (Jurnal Pengabdian Masyarakat - PIMAS, 2026)
Functional academic positions play an essential role in lecturers' academic career development and contribute to improving the quality of higher education institutions. However, limited understanding of the applicable regulations, the preparation of the Credit Score Proposal List (DUPAK), the classification of evidence related to the Tri Dharma of Higher Education, and administrative document requirements remain major challenges in the submission process. To address these issues, a participatory mentoring approach was implemented through five stages: needs identification, socialization, document preparation assistance, document review and verification, and evaluation. The mentoring program was designed to enhance lecturers' understanding and competence in preparing proposal documents in accordance with the applicable regulations, thereby improving their readiness to apply for their first functional academic position. The success of the program was evaluated based on improvements in participants' understanding, their ability to prepare proposal documents, and the completeness of the required submission documents. The program successfully improved participants' understanding of academic promotion regulations, submission procedures, the preparation of the Credit Point Proposal (DUPAK), and credit point calculation. All participants (100%) demonstrated a clear understanding of the promotion process, while three lecturers (50%) successfully completed their first academic promotion application for the Assistant Professor rank. The remaining three participants were unable to submit their applications due to the unavailability of the second-semester Lecturer Workload Report (BKD) for the 2025/2026 academic year, which is a mandatory administrative requirement. Overall, the program enhanced lecturers' readiness to apply for their first academic rank and contributed to strengthening academic career development at Sekolah Tinggi Teknologi Bontang.